Crystal structure of 3-(5-amino-1H-1,2,4-triazol-3-yl)-1-(piperidin-1-yl)propan-1-one, C10H17N5O - Tan Lin Yuing; Lim Felicia Phei Lin; Dolzhenko Anton V.; Tiekink Edward R.T. (Zeitschrift für Kristallographie - New Crystal Structures, 2019)
[C10H17N5O], monoclinic, P21/c (no. 14), a = 8.12150(10) Å, b = 13.2833(2) Å, c = 11.0258(2) Å, β = 110.083(2)°, V = 1117.14(3) Å3, Z = 4, Rgt(F) = 0.0311, wRref(F2) = 0.0790, T = 100(2) K.